2022
DOI: 10.1186/s12905-022-01872-1
|View full text |Cite
|
Sign up to set email alerts
|

“I’m walking on eggshells”: challenges faced by mothers with breast cancer in interacting with adolescent daughters

Abstract: Background With breast cancer becoming the most diagnosed cancer in the world, the number of breast cancer-afflicted mothers with adolescent daughters is also rising. Further, adolescent daughters’ mothers serve as role models for in identity formation processes, especially concerning gender and sexuality. Nevertheless, breast cancer threats mother’s health, including such a key symbol of her womanhood—the breast—which may adversely affect the development of an adolescent daughter’s own sense o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 45 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…However, more research is needed to further analyze this topic. For instance, it might be hypothesized that daughters, with respect to sons, could be more concerned with specific types of cancer that involve female aspects of the body (such as breasts, ovaries, and uterus) [34]. This could be an interesting issue to explore in subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…However, more research is needed to further analyze this topic. For instance, it might be hypothesized that daughters, with respect to sons, could be more concerned with specific types of cancer that involve female aspects of the body (such as breasts, ovaries, and uterus) [34]. This could be an interesting issue to explore in subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…We found that changed family roles due to a mother's breast cancer diagnosis impacted adolescents. Previous research found that mothers experience various challenges in interacting with adolescents about breast cancer due to feelings of guilt, uncertainty about their own life span and how to respond to adolescents' curiosity, and being a mother or patient, leading them to underestimate and ignore adolescents' thoughts and wishes 21,22,24 . Zahlis 67 and Mazaheri et al 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that mothers experience various challenges in interacting with adolescents about breast cancer due to feelings of guilt, uncertainty about their own life span and how to respond to adolescents' curiosity, and being a mother or patient, leading them to underestimate and ignore adolescents' thoughts and wishes. 21,22,24 Zahlis 67 and Mazaheri et al 22 reported that mothers who usually notice small changes in their children's behavior could fail to notice changes due to their shock at a breast cancer diagnosis. Tavares et al 68 report that mothers need support in communicating with their children and dealing with their children's responses and difficult questions related to breast cancer.…”
Section: Supporting Parents May Support Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations